Development of a Colloidal Gold Immunochromatographic Strip for the One-Step Evaluation of the Total Content of Rhein and Aloe-Emodin in Rhubarb - Ping Sun; Xin-Peng Li; Jie Xin; Tao Xue; Bo Zhang; Yan-Juan Liu (International Journal of Analytical Chemistry)
In this study, a colloidal gold immunochromatographic strip was developed for simultaneous detection of rhein and aloe-emodin in rhubarb. The cutoff value, defined as the lowest concentration for which the test line was invisible on the strip, was 50 ng mL−1 for both rhein and aloe-emodin. By contrast, the cutoff value for emodin was 2,000 ng mL−1. No competitive inhibition was observed up to 5,000 ng mL−1 of physcion, chrysophanol, sennoside A, sennoside B, or rhaponticin. Semiquantitative analyses of the total contents of rhein and aloe-emodin in raw drug materials via our colloidal gold immunochromatographic strips produced results agreeable with those determined by HPLC. Taken together, our findings suggest that the implementation of our colloidal gold immunochromatographic strips provides a rapid one-step method for estimating the total contents of rhein and aloe-emodin, which may represent a powerful tool for quality control of rhubarb.